Trajetória escolar de alunos com deficiência : matrículas do censo escolar - Macalli, Ana Carolina (2017)
This research aims to analyze, in three cities of the countryside region of Sao Paulo State, the school trajectory of students with disabilities. In order to do that, we did an official data survey of the cities released by Seade, Human Development Atlas with demographic census data of 2010 and the Municipal Education Plans. Thereafter, we analyzed the micro-data of School Census of Basic Education— made available by INEP (National Institute of Studies and Educational Researches Anísio Teixeira), of the Ministry of Education— regarding the registration of students with disabilities in the years from 2007 to 2015. Thus, we would be able to map the school trajectory of these students. In this study, to choose the cities, we used the following criteria: one city with a high Human Development Index (HDI); one city with an average Human Development Index and one with a very low HDI. 1,782 school trajectories of students with disabilities were analyzed individually and the results show that there are no disparities between the indexes of complete, partial and incomplete trajectories with school retention and age x grade distortion between the cities. This may indicate the adoption of programs, services and/or similar actions for the schooling of this population. We hope that this study can contribute to the discussion in the academic community about the educational reality faced by students with disabilities and, also, contribute to program and policies formulation that aim to establish the permanency and the school success of these students